2012 National Turfgrass Evaluation Program Tall Fescue Test: 2014 Data - L. Parsons; M. Kennelly; J. Griffin; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2015)
A number of the cultivars included in the 2012 National Turfgrass Evaluation Program Tall Fescue Test performed well and showed good brown patch resistance in southern Kansas during the 2014 growing season.
Keywords: brown patch; resistance; tall fescue; transition zone; turfgrass